2013
DOI: 10.1159/000354136
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Pancreatic Fistula after Distal Pancreatectomy and Efficacy of Endoscopic Therapy for Its Management: Results from a Tertiary Care Center

Abstract: Pancreatic fistula is a known complication of distal pancreatectomy. Endotherapy with pancreatic duct stent placement and pancreatic sphincterotomy has been shown to be effective in its management; however, experience of endotherapy in the management of this complication has not been extensively reported from the United States. Preoperative endoscopic retrograde cholangiopancreatography (ERCP) with pancreatic stent placement has also been proposed to prevent this complication after distal pancreatectomy. In ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Watanabe et al [ 25 ] demonstrated a similar hospital stay with or without ET (40 days) and the mean healing time after ET was 46 days in 11 patients. Reddymasu et al [ 28 ] reported healing in eight patients 44–379 days after ET. Goasguen et al [ 26 ] evaluated ten patients (including two enucleations) who underwent ET, experiencing a POPF resolution after 1–12 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Watanabe et al [ 25 ] demonstrated a similar hospital stay with or without ET (40 days) and the mean healing time after ET was 46 days in 11 patients. Reddymasu et al [ 28 ] reported healing in eight patients 44–379 days after ET. Goasguen et al [ 26 ] evaluated ten patients (including two enucleations) who underwent ET, experiencing a POPF resolution after 1–12 days.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the placement of a stent in the MPD could facilitate fistula resolving. However, this treatment adjunct has only been scarcely evaluated, and so far, without any promising results [ 25 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have established that a pancreatic leak or fistula postoperatively constitutes a risk factor for a delayed hemorrhage, presumably because the leak can lead to abscess formation and weaken the surrounding tissue and blood vessels, thereby increasing the potential for hemorrhage [2628]. The rate of pancreatic fistula after pancreaticoduodenectomy and distal pancreatectomy has been reported to be has high as 28% [29, 30]. As such, if a patient were to develop a VTE and need to be placed on therapeutic anticoagulation, they may be at increased risk for bleeding in the setting of a leak [31].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, radiologically guided external drainage may cause localized skin irritation and infections, prolongs the duration of treatment (especially in collections associated with distal pancreatectomy and enucleation), delays oral re-feeding, and implies a longer hospital stay [29]. The use of endoscopic ultrasound (EUS)-guided transmural drainage, initially applied for management of pseudocysts secondary to acute pancreatitis, has grown in frequency to drain collections associated with POPF, after both PD and distal pancreatectomy [30,31]. Briefly, an FNA needle is used to puncture through the gastric wall into the fluid collection.…”
Section: Interventional Techniquesmentioning
confidence: 99%